If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -1wx = vx + 2 Reorder the terms: 6 + -1wx = 2 + vx Solving 6 + -1wx = 2 + vx Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1wx = 2 + -6 + vx Combine like terms: 6 + -6 = 0 0 + -1wx = 2 + -6 + vx -1wx = 2 + -6 + vx Combine like terms: 2 + -6 = -4 -1wx = -4 + vx Divide each side by '-1x'. w = 4x-1 + -1v Simplifying w = 4x-1 + -1v Reorder the terms: w = -1v + 4x-1
| 3=6+x/4 | | 9+(0.5x)= | | -5x+3=8 | | x(x-7)=458 | | 2/5y+3=6 | | 0.12-0.01(x+3)=-0.03(1-x) | | Y/3+25=48 | | 3/4p+7=16 | | 3/x=2/x-1 | | 31+w/3=31 | | k/8-9=6 | | 32+90x=78x+78 | | x/5-3=x/7-1 | | 4x+43=139 | | 22x+8x=160+22x | | 8(2x+1)-(x+3)=35 | | 39+3m=174 | | 4x+6x+50=20 | | 4x-26=2x+65 | | 42x^3-35x^2+14x=0 | | -7+x=8 | | 2(6v+7)=10(v+8) | | -1/2+3x=1 | | 35+3g=71 | | 8+x/7=16 | | 3x(7)-x=127 | | 6(3n+3)=6(7n+3)+5 | | x^3-8x^2-5x+40=0 | | 15=2m-3 | | 12+x/11=9 | | x(x)+15x=-56 | | 2.2x-2.4=13 |